Nudging against insider trading - Chyngyz, Emir; Cingl, Lubomír, 1984-; Miklánek, Tomáš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis investigates whether behavioral nudges can effectively deter insider trading within financial institutions. While insider trading remains illegal and is subject to legal sanctions, its persistence highlights the limitations of traditional deterrence mechanisms. Building on behavioral economics and regulatory compliance literature, this study evaluates four nudging strategies: a plain reminder, public disclosure, prison sentence framing, and commission framing. A cluster randomized controlled trial was proposed with 175 hypothetical financial institutions to assess the efficacy of these interventions in reducing suspicious trading behavior. Behaviorally informed messages are likely to reduce the risk of insider trading, especially when they emphasize reputational consequences or the threat of jail time. This research contributes to the growing field of behavioral regulation and proposes novel tools for enhancing ethical behavior in financial markets.
Vedoucí práce: Lubomír Cingl
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses